Biosynthesis of antinutritional alkaloids in solanaceous crops is mediated by clustered genes - Itkin, M.; Heinig, U.; Tzfadia, O.; Bhide, Amey J.; Shinde, B.; Cardenas, Pablo D.; Bocobza, S. E.; Unger, T.; Malitsky, Sergey; Finkers, R.; Tikunov, Y.; Bovy, A.; et al. (Science, 2013)
Steroidal glycoalkaloids (SGAs) such as alpha-solanine found in solanaceous food plants-as, for example, potato-are antinutritional factors for humans. Comparative coexpression analysis between tomato and potato coupled with chemical profiling revealed an array of 10 genes that partake in SGA biosynthesis. We discovered that six of them exist as a cluster on chromosome 7, whereas an additional two are adjacent in a duplicated genomic region on chromosome 12. Following systematic functional analysis, we suggest a revised SGA biosynthetic pathway starting from cholesterol up to the tetrasaccharide moiety linked to the tomato SGA aglycone. Silencing GLYCOALKALOID METABOLISM 4 prevented accumulation of SGAs in potato tubers and tomato fruit. This may provide a means for removal of unsafe, antinutritional substances present in these widely used food crops.

GAME9 regulates the biosynthesis of steroidal alkaloids and upstream isoprenoids in the plant mevalonate pathway - Cardenas, Pablo D.; Sonawane, Prashant D.; Pollier, Jacob; Vanden Bossche, Robin; Dewangan, Veena; Weithorn, Efrat; Tal, Lior; Meir, Sagit; Rogachev, Ilana; Malitsky, Sergey; Giri, Ashok P.; Goossens, Alain; et al. (Nature Communications, 2016)
Steroidal glycoalkaloids (SGAs) are cholesterol-derived molecules produced by solanaceous species. They contribute to pathogen defence but are toxic to humans and considered as anti-nutritional compounds. Here we show that GLYCOALKALOID METABOLISM 9 (GAME9), an APETALA2/Ethylene Response Factor, related to regulators of alkaloid production in tobacco and Catharanthus roseus, controls SGA biosynthesis. GAME9 knockdown and overexpression in tomato and potato alters expression of SGAs and upstream mevalonate pathway genes including the cholesterol biosynthesis gene STEROL SIDE CHAIN REDUCTASE 2 (SSR2). Levels of SGAs, C24-alkylsterols and the upstream mevalonate and cholesterol pathways intermediates are modified in these plants. Delta(7)-STEROL-C5(6)-DESATURASE (C5-SD) in the hitherto unresolved cholesterol pathway is a direct target of GAME9. Transactivation and promoter-binding assays show that GAME9 exerts its activity either directly or cooperatively with the SlMYC2 transcription factor as in the case of the C5-SD gene promoter. Our findings provide insight into the regulation of SGA biosynthesis and means for manipulating these metabolites in crops.

Dynamic metabolic reprogramming of steroidal glycol-alkaloid and phenylpropanoid biosynthesis may impart early blight resistance in wild tomato (Solanum arcanum Peralta) - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Panda, Sayantan; Meir, Sagit; Rogachev, Ilana; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Molecular Biology, 2017)
Alternaria solani severely affects tomato (Solanum lycopersicum L.) yield causing early blight (EB) disease in tropical environment. Wild relative, Solanum arcanum Peralta could be a potential source of EB resistance; however, its underlying molecular mechanism largely remains unexplored. Hence, non-targeted metabolomics was applied on resistant and susceptible S. arcanum accessions upon A. solani inoculation to unravel metabolic dynamics during different stages of disease progression. Total 2047 potential metabolite peaks (mass signals) were detected of which 681 and 684 metabolites revealed significant modulation and clear differentiation in resistant and susceptible accessions, respectively. Majority of the EB-triggered metabolic changes were active from steroidal glycol-alkaloid (SGA), lignin and flavonoid biosynthetic pathways. Further, biochemical and gene expression analyses of key enzymes from these pathways positively correlated with phenotypic variation in the S. arcanum accessions indicating their potential role in EB. Additionally, transcription factors regulating lignin biosynthesis were also up-regulated in resistant plants and electrophoretic mobility shift assay revealed sequence-specific binding of rSaWRKY1 with MYB20 promoter. Moreover, transcript accumulation of key genes from phenylpropanoid and SGA pathways along with WRKY and MYB in WRKY1 transgenic tomato lines supported above findings. Overall, this study highlights vital roles of SGAs as phytoalexins and phenylpropanoids along with lignin accumulation unrevealing possible mechanistic basis of EB resistance in wild tomato.

WRKY1 acts as a key component improving resistance against Alternaria solani in wild tomato, Solanum arcanum Peralta - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Biotechnology Journal, 2018)
Early blight (EB), caused by Alternaria solani, is a major threat to global tomato production. In comparison with cultivated tomato (Solanum lycopersicum), a wild relative, S.arcanum exhibits strong resistance against EB. However, molecular cascades operating during EB resistance in wild or cultivated tomato plants are largely obscure. Here, we provide novel insight into spatio-temporal molecular events in S.arcanum against A.solani. Transcriptome and co-expression analysis presented 33-WRKYs as promising candidates of which 12 SaWRKYs displayed differential expression patterns in resistant and susceptible accessions during EB disease progression. Among these, SaWRKY1 exhibited induced expression with significant modulation in xyloglucan endotrans hydrolase 5 (XTH5) and MYB2 expressions that correlated with the disease phenotypes. Electro-mobility shift assay confirmed physical interaction of recombinant SaWRKY1 to SaXTH5 and SaMYB2 promoters. Comparative WRKY1 promoter analysis between resistant and susceptible plants revealed the presence of crucial motifs for defence mechanism exclusively in resistant accession. Additionally, many defence-related genes displayed significant expression variations in both the accessions. Further, WRKY1 overexpressing transgenic plants exhibited higher levels of EB resistance while RNAi silencing lines had increased susceptibility to A.solani with altered expression of XTH5 and MYB2. Overall, these findings demonstrate the positive influence of WRKY1 in improving EB resistance in wild tomato and this could be further utilized as a potential target through genetic engineering to augment protection against A.solani in crop plants.
Keywords: Alternaria solani; early blight; Solanum arcanum; Tomato; WRKY1; XTH5

Pathways to defense metabolites and evading fruit bitterness in genus Solanum evolved through 2-oxoglutarate-dependent dioxygenases - Cardenas, Pablo D.; Sonawane, Prashant D.; Heinig, Uwe; Jozwiak, Adam; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Pliner, Margarita; Unger, Tamar; Wolf, Dalia; Ofner, Itai; Vilaprinyo, Ester; et al. (Nature Communications, 2019)
The genus Solanum comprises three food crops (potato, tomato, and eggplant), which are consumed on daily basis worldwide and also producers of notorious anti-nutritional steroidal glycoalkaloids (SGAs). Hydroxylated SGAs (i.e. leptinines) serve as precursors for leptines that act as defenses against Colorado Potato Beetle (Leptinotarsa decemlineata Say), an important pest of potato worldwide. However, SGA hydroxylating enzymes remain unknown. Here, we discover that 2-OXOGLUTARATE-DEPENDENT-DIOXYGENASE (2-ODD) enzymes catalyze SGA-hydroxylation across various Solanum species. In contrast to cultivated potato, Solanum chacoense, a widespread wild potato species, has evolved a 2-ODD enzyme leading to the formation of leptinines. Furthermore, we find a related 2-ODD in tomato that catalyzes the hydroxylation of the bitter a-tomatine to hydroxytomatine, the first committed step in the chemical shift towards downstream ripening-associated non-bitter SGAs (e.g. esculeoside A). This 2-ODD enzyme prevents bitterness in ripe tomato fruit consumed today which otherwise would remain unpleasant in taste and more toxic.

2-oxoglutarate-dependent dioxygenases drive expansion of steroidal alkaloid structural diversity in the genus Solanum - Sonawane, Prashant D.; Jozawiak, Adam; Barbole, Ranjit; Panda, Sayantan; Abebie, Bekele; Kazachkova, Yana; Gharat, Sachin A.; Ramot, Ofir; Unger, Tamar; Wizler, Guy; Meir, Sagit; Rogachev, Ilana; et al. (New Phytologist, 2022)
Solanum steroidal glycoalkaloids (SGAs) are renowned defence metabolites exhibiting spectacular structural diversity. Genes and enzymes generating the SGA precursor pathway, SGA scaffold and glycosylated forms have been largely identified. Yet, the majority of downstream metabolic steps creating the vast repertoire of SGAs remain untapped. Here, we discovered that members of the 2-OXOGLUTARATE-DEPENDENT DIOXYGENASE (2-ODD) family play a prominent role in SGA metabolism, carrying out three distinct backbone-modifying oxidative steps in addition to the three formerly reported pathway reactions. The GLYCOALKALOID METABOLISM34 (GAME34) enzyme catalyses the conversion of core SGAs to habrochaitosides in wild tomato S. habrochaites. Cultivated tomato plants overexpressing GAME34 ectopically accumulate habrochaitosides. These habrochaitoside enriched plants extracts potently inhibit Puccinia spp. spore germination, a significant Solanaceae crops fungal pathogen. Another 2-ODD enzyme, GAME33, acts as a desaturase (via hydroxylation and E/F ring rearrangement) forming unique, yet unreported SGAs. Conversion of bitter alpha-tomatine to ripe fruit, nonbitter SGAs (e.g. esculeoside A) requires two hydroxylations; while the known GAME31 2-ODD enzyme catalyses hydroxytomatine formation, we find that GAME40 catalyses the penultimate step in the pathway and generates acetoxy-hydroxytomatine towards esculeosides accumulation. Our results highlight the significant contribution of 2-ODD enzymes to the remarkable structural diversity found in plant steroidal specialized metabolism.
Keywords: Solanum; specialized metabolism; steroidal glycoalkaloids (SGAs); structural diversity; Tomato

Identification and characterization of the key enzyme in the biosynthesis of the neurotoxin beta-ODAP in grass pea - Goldsmith, Moshe; Barad, Shiri; Knafo, Maor; Savidor, Alon; Ben-Dor, Shifra; Brandis, Alexander; Mehlman, Tevie; Peleg, Yoav; Albeck, Shira; Dym, Orly; Ben-Zeev, Efrat; Barbole, Ranjit S.; et al. (Journal of Biological Chemistry, 2022)
Grass pea (Lathyrus sativus L.) is a grain legume commonly grown in Asia and Africa for food and forage. It is a highly nutritious and robust crop, capable of surviving both droughts and floods. However, it produces a neurotoxic compound, beta-N- oxalyl-L-alpha,beta-diaminopropionic acid (beta-ODAP), which can cause a severe neurological disorder when consumed as a primary diet component. While the catalytic activity associated with beta-ODAP formation was demonstrated more than 50 years ago, the enzyme responsible for this activity has not been identified. Here, we report on the identity, activity, 3D structure, and phylogenesis of this enzyme-beta-ODAP synthase (BOS). We show that BOS belongs to the benzylalcohol O-acetyltransfer-ase, anthocyanin O-hydroxycinnamoyltransferase, anthranilate N-hydroxycinnamoyl/benzoyltransferase, deacetylvindoline 4-O-acetyltransferase superfamily of acyltransferases and is structurally similar to hydroxycinnamoyl transferase. Using molecular docking, we propose a mechanism for its catalytic activity, and using heterologous expression in tobacco leaves (Nicotiana benthamiana), we demonstrate that expression of BOS in the presence of its substrates is sufficient for beta-ODAP production in vivo. The identification of BOS may pave the way toward engineering beta-ODAP-free grass pea cultivars, which are safe for human and animal consumption.

Steroidal alkaloids defence metabolism and plant growth are modulated by the joint action of gibberellin and jasmonate signalling - Panda, Sayantan; Jozwiak, Adam; Sonawane, Prashant D.; Szymanski, Jedrzej; Kazachkova, Yana; Vainer, Andrii; Kilambi, Himabindu Vasuki; Almekias-Siegl, Efrat; Dikaya, Varvara; Bocobza, Samuel; Shohat, Hagai; Meir, Sagit; et al. (New Phytologist, 2022)
Steroidal glycoalkaloids (SGAs) are protective metabolites constitutively produced by Solanaceae species. Genes and enzymes generating the vast structural diversity of SGAs have been largely identified. Yet, mechanisms of hormone pathways coordinating defence (jasmonate; JA) and growth (gibberellin; GA) controlling SGAs metabolism remain unclear. We used tomato to decipher the hormonal regulation of SGAs metabolism during growth vs defence tradeoff. This was performed by genetic and biochemical characterisation of different JA and GA pathways components, coupled with in vitro experiments to elucidate the crosstalk between these hormone pathways mediating SGAs metabolism. We discovered that reduced active JA results in decreased SGA production, while low levels of GA or its receptor led to elevated SGA accumulation. We showed that MYC1 and MYC2 transcription factors mediate the JA/GA crosstalk by transcriptional activation of SGA biosynthesis and GA catabolism genes. Furthermore, MYC1 and MYC2 transcriptionally regulate the GA signalling suppressor DELLA that by itself interferes in JA-mediated SGA control by modulating MYC activity through protein-protein interaction. Chemical and fungal pathogen treatments reinforced the concept of JA/GA crosstalk during SGA metabolism. These findings revealed the mechanism of JA/GA interplay in SGA biosynthesis to balance the cost of chemical defence with growth.
Keywords: alpha-tomatine; defence; gibberellin (GA); growth; jasmonate (JA); steroidal glycoalkaloids (SGAs); Tomato

BAHD-type acyltransferase concludes the biosynthetic pathway of non-bitter glycoalkaloids in ripe tomato fruit - Sonawane, Prashant D.; Gharat, Sachin A.; Jozwiak, Adam; Barbole, Ranjit; Heinicke, Sarah; Almekias-Siegl, Efrat; Meir, Sagit; Rogachev, Ilana; O'Connor, Sarah E.; Giri, Ashok P.; Aharoni, Asaph (Nature Communications, 2023)
During tomato fruit ripening, bitter and toxic steroidal glycoalkaloids (SGAs) are converted to nonbitter and less toxic forms, but proposed acylating enzyme in pathway remain unknown. Here, authors report BAHD-type acyltransferase that catalyze acylation step in biosynthesis of non-bitter SGAs in tomato. Tomato is the highest value fruit and vegetable crop worldwide, yet produces & alpha;-tomatine, a renowned toxic and bitter-tasting anti-nutritional steroidal glycoalkaloid (SGA) involved in plant defense. A suite of modifications during tomato fruit maturation and ripening converts & alpha;-tomatine to the non-bitter and less toxic Esculeoside A. This important metabolic shift prevents bitterness and toxicity in ripe tomato fruit. While the enzymes catalyzing glycosylation and hydroxylation reactions in the Esculeoside A pathway have been resolved, the proposed acetylating step remains, to date, elusive. Here, we discovered that GAME36 (GLYCOALKALOID METABOLISM36), a BAHD-type acyltransferase catalyzes SGA-acetylation in cultivated and wild tomatoes. This finding completes the elucidation of the core Esculeoside A biosynthetic pathway in ripe tomato, allowing reconstitution of Esculeoside A production in heterologous microbial and plant hosts. The involvement of GAME36 in bitter SGA detoxification pathway points to a key role in the evolution of sweet-tasting tomato as well as in the domestication and breeding of modern cultivated tomato fruit.

Parallel evolution of cannabinoid biosynthesis - Berman, Paula; de Haro, Luis Alejandro; Jozwiak, Adam; Panda, Sayantan; Pinkas, Zoe; Dong, Younghui; Cveticanin, Jelena; Barbole, Ranjit; Livne, Rotem; Scherf, Tali; Shimoni, Eyal; Levin-Zaidman, Smadar; et al. (Nature Plants, 2023)
This study reveals a cannabinoid biosynthetic pathway in Helichrysum umbraculigerum, a plant genetically distant from Cannabis, providing a potential source of new cannabinoids and metabolic engineering tools. Modulation of the endocannabinoid system is projected to have therapeutic potential in almost all human diseases. Accordingly, the high demand for novel cannabinoids stimulates the discovery of untapped sources and efficient manufacturing technologies. Here we explored Helichrysum umbraculigerum, an Asteraceae species unrelated to Cannabis sativa that produces Cannabis-type cannabinoids (for example, 4.3% cannabigerolic acid). In contrast to Cannabis, cannabinoids in H. umbraculigerum accumulate in leaves' glandular trichomes rather than in flowers. The integration of de novo whole-genome sequencing data with unambiguous chemical structure annotation, enzymatic assays and pathway reconstitution in Nicotiana benthamiana and in Saccharomyces cerevisiae has uncovered the molecular and chemical features of this plant. Apart from core biosynthetic enzymes, we reveal tailoring ones producing previously unknown cannabinoid metabolites. Orthology analyses demonstrate that cannabinoid synthesis evolved in parallel in H. umbraculigerum and Cannabis. Our discovery provides a currently unexploited source of cannabinoids and tools for engineering in heterologous hosts.

Navigating the challenges of engineering composite specialized metabolite pathways in plants - Gharat, Sachin A.; Tamhane, Vaijayanti A.; Giri, Ashok P.; Aharoni, Asaph (Plant Journal, 2025)
Plants are a valuable source of diverse specialized metabolites with numerous applications. However, these compounds are often produced in limited quantities, particularly under unfavorable ecological conditions. To achieve sufficient levels of target metabolites, alternative strategies such as pathway engineering in heterologous systems like microbes (e.g., bacteria and fungi) or cell-free systems can be employed. Another approach is plant engineering, which aims to either enhance the native production in the original plant or reconstruct the target pathway in a model plant system. Although increasing metabolite production in the native plant is a promising strategy, these source plants are often exotic and pose significant challenges for genetic manipulation. Effective pathway engineering requires comprehensive prior knowledge of the genes and enzymes involved, as well as the precursor, intermediate, branching, and final metabolites. Thus, a thorough elucidation of the biosynthetic pathway is closely linked to successful metabolic engineering in host or model systems. In this review, we highlight recent advances in strategies for biosynthetic pathway elucidation and metabolic engineering. We focus on efforts to engineer complex, multi-step pathways that require the expression of at least eight genes for transient and three genes for stable transformation. Reports on the engineering of complex pathways in stably transformed plants remain relatively scarce. We discuss the major hurdles in pathway elucidation and strategies for overcoming them, followed by an overview of achievements, challenges, and solutions in pathway reconstitution through metabolic engineering. Recent advances including computer-based predictions offer valuable platforms for the sustainable production of specialized metabolites in plants.
Keywords: Biosynthetic pathway; Enzyme activity; Gene expression; Metabolic engineering; Metabolites